Osteoporosis: A silent epidemic - Yusimí Isaguirre Martínez (Medisur, 2006)
Nowadays most persons know about the human immunodeficiency virus, hypertension and other diseases. People know about their characteristics and the way to fight them. Thanks to the media campaigns and the family physician activity, there are few transmissible and not transmissible diseases people do not have any reference about. There is a disease of which little is spoken; nevertheless, each day augments the number of people that suffer from it. This almost unknown illness is named: osteoporosis and constitutes the motive of the present work.